If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-3x-12(3)=5x+24x=
We move all terms to the left:
9x-3x-12(3)-(5x+24x)=0
We add all the numbers together, and all the variables
9x-3x-(+29x)-123=0
We add all the numbers together, and all the variables
6x-(+29x)-123=0
We get rid of parentheses
6x-29x-123=0
We add all the numbers together, and all the variables
-23x-123=0
We move all terms containing x to the left, all other terms to the right
-23x=123
x=123/-23
x=-5+8/23
| 4(4)+8-2m=3(m+4) | | 0.2x+0.6=3.0 | | 3x-8=-14* | | | | 0.3x-1.5=4.5 | | 7q-5=12q+30* | | 3x2−5x−8=0 | | 3(x-2.4=4x+4 | | 6s+3=57 | | 6d+18=30 | | 6(-6-5v)=86 | | m-32=-66 | | 7m-9=4 | | 8=y÷14 | | 1/5(r+0.5)+5.24=3/2r+7/10(r+2.2) | | 9y-5=15y-17* | | 69d+15=429 | | 15=x÷2 | | 8=14y | | 5c-6=2c+15 | | 4(5z-7)=88 | | 3(2x+4)=5(x+4) | | 14=8y | | 4x-2x+6=10x-2 | | 3z/10-5=-6 | | 2w+2(2w+3)=804 | | 6t+2=32 | | -9r=-7r+8 | | 16-4m=m | | 14d+45=101 | | -2.4=(x-70/10) | | 60+x+20=180 |